The study of social sustainability and liveliness in Jalan Wong Ah Fook, Johor Bahru - Khadem Zadeh, Mohammad Reza (2012)
Street is considered the major public space in urban fabric. It acts as a meeting place for different social groups and urban activities. Among the different types of street is where carriageway space has been recognized to pedestrian use. In order to invite leisure walking and numerous social and economic activities, pedestrian streets try to make city centre more pedestrian friendly and lively that involves the presence of an active street life. As liveliness is derived from the way activity, this study aimed to provide rich and detailed information on the liveliness of pedestrian streets in the context of Johor Bahru. In this case, physical and social attributes of place making is utilized to examine which criteria have influence on user‘s perception and satisfaction in the street with Jalan Wong Ah Fook, Johor Bahru as a case study. This study adopts the questionnaire survey as a quantitative method to evaluate resident‘s perception while the observation survey was used confirm findings the aforementioned method. The research findings proved that accessibility to open space, facilities and amenities as physical indicators in one hand, and on the other hand safety, privacy and social interaction as social attributes of place making play a significant role on creating quality of street, use and satisfaction. The general results of this study noted that both physical and social attributes of place making have influence on the presence of users within a street. Also the study appraise present some suggestions for improving the quality of street as a main indicator to enhance better quality of living.